Collaborative referencing using hand gestures in Wernicke's aphasia: Discourse analysis of a case study. Issue 9 (2nd September 2022) - Devanga, Suma R.; Wilgenhof, Rachel; Mathew, Mili
ABSTRACT: Background : Collaborative referencing tasks have evolved from historically being used as experiments to study human interactions in various disciplines, to being adapted as a clinical intervention for individuals with cognitive-communication disorders such as aphasia. For both neurotypical adults and adults with cognitive-communication disorders, evidence on successful referencing is heavily based on spoken language data. The patterns of collaborative referencing in individuals with severe spoken language impairments who extensively use hand gestures for communication remain unclear. Aims : We aimed to investigate the patterns of collaborative referencing between Clyde, an individual with severe Wernicke's aphasia using co-speech hand gestures, and a clinician-partner during the collaborative referencing intervention (CRI). Methods & Procedures : This case study included 15 CRI sessions between Clyde and the clinician-partner. Each session consisted of a photo-matching game in which the pair completed six trials with alternating turns to describe and match treatment cards over a low barrier. Data analysis included (a) measuring the mean card placement accuracy; (b) measuring the mean length of CRI trials; and (c) analysing the frequency and type of hand gestures used in no common ground and common ground conditions, and then examining if the multimodal references (i.e., labels for treatment cards produced using verbal expressions and hand gestures) simplified across CRI sessions. Outcomes & Results : Largely, the results were consistent with previous evidence on CRI: the pair scored 99.63% mean card placement accuracy and completed each trial in shorter time periods, indicating reduced collaborative effort. During the no common ground condition, the pair used a high frequency of hand gestures and a variety of gesture-type combinations to reference each card, while they used a low frequency of hand gestures dominated by iconic gestures in the common ground condition. The multimodal references were found to be simplified across sessions by the shift from using indefinite to definite verbal references, and reduced frequency and specific (iconic) types of hand gestures. Conclusions : Despite severe spoken language impairments, speakers and partners can develop common ground for successful collaborative referencing by effectively using hand gestures. Clinical implications including the role of clinicians in being a skilful and multimodal communication partner and the rich communicative environment offered by CRI will be discussed.